2011
DOI: 10.2528/pier11010303
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Results on a Planar Array of Parasitic Dipoles Fed by One Active Element

Abstract: Abstract-A planar array composed of 41 parasitic dipoles above a ground plane, fed by an active dipole at 5 GHz, was designed to obtain a pencil beam pattern with a moderate gain and bandwidth. Experimental results are in good agreement with the theory and show a pattern with an 18.78 dB gain, a sidelobe level (SLL) of −15 dB, an impedance bandwidth of 16.53% (the frequency range over which the value of S 11 is below −10 dB) and a 2.7% bandwidth that is achieved within 1 dB gain variations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
(22 reference statements)
0
6
0
Order By: Relevance
“…One way to reduce the complexity and cost of an array antenna is to eliminate the need for a complex feed network by feeding parasitic elements via a single active element . The elements that are not directly driven, called parasites, receive their excitations from the driven element through field coupling.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One way to reduce the complexity and cost of an array antenna is to eliminate the need for a complex feed network by feeding parasitic elements via a single active element . The elements that are not directly driven, called parasites, receive their excitations from the driven element through field coupling.…”
Section: Introductionmentioning
confidence: 99%
“…In , we designed a 48‐parasite pencil beam array with moderate gain and bandwidth using the method of moments as implemented in FEKO simulation software and its particle swarm optimization module. Here, we describe the design and construction of a similar array, more compact than that of , with optimized directivity and impedance matching a 50 Ω feedline. Measurements of its characteristics with and without a protective radome agree well with theory.…”
Section: Introductionmentioning
confidence: 99%
“…Each element, in the presence of others, acquires a phased-up transscattering capability. In a further work, this design was validated by means of a prototype, where experimental results showed a good agreement with the expected ones [22].…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of the equivalent dipole distribution will allow the study of multiple dipole scattering structures [37], as suggested for a 2D obstacle distribution in Fig. 14.…”
Section: Equivalent Dipole Approximationmentioning
confidence: 99%